Recovering Washington's Body-Double: Disability and Manliness in the Life and Legacy of a Founding Father - Foster, Thomas A. (Disability Studies Quarterly, 2012)
This essay closely examines early American Founder, Gouverneur Morris's personal diaries that he kept while in Paris from 1789 to 1793. Morris's writings make him an obvious candidate for a case study that uses recent and developing literature on the histories of early American disability, sexuality, and masculinity to try to understand Morris's historical context and experiences. Historical memory of Morris depicts his mobility impairment as a personal challenge that he overcame. Although he experienced some negative responses from able-bodied individuals in both America and Europe, he lived in a world that had moved past viewing disability as a physical marker of Godlessness but that had not yet embraced the modern medicalized conceptualization of abnormality and accompanying institutional discrimination. Morris's diaries offer a rare glimpse at the experiences and identity of an eighteenth-century American with a disability. Keywords sexuality, early America, disability, Founding Father, masculinity